DECLINE OF ADAPTIVE HOMEOSTASIS & HORMESIS IN AGING. (11th November 2018) - Curran, S
Abstract: Maintenance of cell- and organism-level homeostasis across the lifespan is essential for healthy aging. The biological mechanisms that govern homeostasis are complex and can impact organism health and longevity. Adaptive Homeostasis is the transient modulation of stress-protective processes that enables organisms to cope with constant perturbations, ensuring optimal function. The Nrf2 transcriptionally-regulated target enzymes show rapid induction in young organisms, but is lost with age, suggesting declining inducibility of the adaptive homeostatic response may be a contributor to aging. The chronic activation of cytoprotection pathways can lead to pleiotropic outcomes. In C. elegans, activated SKN-1/NRF2 stemming from defective mitochondrial homeostasis, drives early reproductive senescence in males. The endocrine system integrates physiological systems to maintain homeostasis, in part, by regulating metabolism. Reduced signaling of growth hormone alters the metabolism of methionine, upregulates defense mechanisms and maintains young DNA methylation patterns, all of which lead to lifespan extension in rodents. In the past decade, it has become clear that the antidiabetic drug metformin also has anti-aging properties. Genetic approaches indicate that the metformin pro-longevity pathway is highly conserved from worm to human and involves reversal of aging-associated nuclear leakiness and suppression of mTOR signaling. Homeostasis is maintained at all hierarchical levels (from molecules to organism) and requires constant surveillance throughout the lifespan. As our understanding of the intricacies of this regulation are developed so will our capacity to capitalize on these systems to improve health across the lifespan.